1985
DOI: 10.2307/3429885
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Biosynthesis of Methylsulfones from PCBs and Related Compounds

Abstract: , methylthio-, methylsulfinyl-and methysulfonyl metabolites of PCBs, 2,5,2',5'-tetrachlorobiphenyl, 1,3,5-trichlorobenzene and some other chlorobenzenes were identified in adipose tissues of mice, rats and guinea pigs by using GC/MS/COM systems. By means of administration of CD3-methionine, it was confirmed that the methyl group in methylthio metabolites was derived from the methionine. Moreover, after pretreatment with either esterification of urinary metabolites in guinea pigs with 1,3,5-trichlorobenzene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…POPs are detectable in virtually everyone, with exposure occurring through fatty animal food in particular [21]. Some POPs are conjugated to GSH for their metabolism [22][23][24], and exposure to high amounts of certain POPs in occupational or accidental settings increase serum GGT activity [25,26].…”
Section: Serum Ggt Activity As a Marker Of Exposure To Popsmentioning
confidence: 99%
“…POPs are detectable in virtually everyone, with exposure occurring through fatty animal food in particular [21]. Some POPs are conjugated to GSH for their metabolism [22][23][24], and exposure to high amounts of certain POPs in occupational or accidental settings increase serum GGT activity [25,26].…”
Section: Serum Ggt Activity As a Marker Of Exposure To Popsmentioning
confidence: 99%
“…The structure-tissue affinity relationship study demonstrated that retention potential of live metabolites largely depends on the ortho -chlorine substitution and not the degree of chlorination. Interestingly, hydroxylated methylsulfonyl metabolites were discovered in the urine of mice that were treated with PCBs …”
Section: Metabolic Pathway Yielding Sulfur-containing Metabolitesmentioning
confidence: 99%
“…Interestingly, hydroxylated methylsulfonyl metabolites were discovered in the urine of mice that were treated with PCBs. 102 The rate of formation of MeSO 2 -metabolites is largely dependent on the degree of chlorination, that is, the less chlorinated congeners (tri-or tetra-) metabolize more rapidly than higher chlorinated ones (penta-or hexa-). 103 It is interesting to notice that 3-methylsulfonyl derivatives from a higher degree PCB have a relatively high affinity in liver and adipose tissues, whereas 4-methylsulfonyl derivatives have a relatively high affinity in lungs.…”
Section: Metabolic Pathway Yielding Sulfur-containing Metabolitesmentioning
confidence: 99%
“…The other two, M b and M c , were presumably the precursors of M d because when the fraction was oxidized chemically, the two peaks were converted to the corresponding methylsulfones (M d ). Mio and Sumino (1985) identified 3-hydroxy-4-methylthio-2,5,2Ј,5Ј-tetraCB in the feces from rats, mice, and guinea pigs dosed with 2,5,2Ј,5Ј-tetraCB, suggesting that the precursor of the metabolite was 3,4-epoxide. The epoxide may have been opened by nucleophile attack of the sulfhydryl group and subsequently converted to the hydroxylated metabolite by dehydrogenation (Bakke et al, 1982).…”
Section: Haraguchi Et Almentioning
confidence: 99%